Maritime Power of India: An Analysis on Maritime Issues with Pakistan, Bangladesh and Sri Lanka: The Growing Geopolitical Significance of the Indian Ocean (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The geopolitics of the Indian Ocean has for a long while been away from consequence of the closeness of the fundamental ocean paths of correspondences. The Indian Ocean is the third greatest ocean on earth and is a key travel region between territory trade vitality and business products. While its essentialness as a transportation place point is depended upon to augment further all through the next decades and it is in like manner continuously transforming into a trade objective its own right. The ocean paths in the Indian Ocean are considered among the most deliberately huge on earth. It isn't just ocean paths and trade yet furthermore most of the world's prepared conflicts are in like manner before long arranged in the Indian Ocean Region (IOR). The IOR has been consistently a valuable region for the exchange, security, marine resources to the littoral states just as prevailing world powers of the time. Thusly, Asia's geopolitics is being formed by this basic sea center point as a result of the significance of Indian Ocean regarding the contemporary issues of geo-politics, geo-economics and geo-strategic. As indicated by Geoffrey Till, there are four key and reliant qualities of sea power the sea as a mode for exchange and as an asset, as far as what exists in its waters the sea as a mechanism for educational and cultural exchange just as a vehicle of domain. The IOR has every one of these ascribes this prompts its expanding geopolitical hugeness in world politics.